2018
DOI: 10.1039/c7cc07549a
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial activity of polyoxometalates: structures, antibiotic effects and future perspectives

Abstract: This Feature Article focuses on the antibacterial activity of POMs and POM-based hybrid and nanocomposite structures highlighting recent advances in the synthesis of biologically active POM systems and providing the state of the art in this research field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
230
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 333 publications
(234 citation statements)
references
References 104 publications
(125 reference statements)
1
230
0
3
Order By: Relevance
“…POMs exert significant biological activities, with high efficacy and low toxicity. With regards to the biological activity of the POMs, many literature reports describe the activity of polyoxometalates with Keggin, lacunary Keggin, Wells-Dawson, double-Keggin and Keggin-sandwich structures against methicillin-resistant Staphylococcus aureus (MRSA) [16], Helicobacter pylori [17], SARS coronavirus (SARS-CoV) [18] and Cancer [19]. With regards to the biological activity of the POMs, many literature reports describe the activity of polyoxometalates with Keggin, lacunary Keggin, Wells-Dawson, double-Keggin and Keggin-sandwich structures against methicillin-resistant Staphylococcus aureus (MRSA) [16], Helicobacter pylori [17], SARS coronavirus (SARS-CoV) [18] and Cancer [19].…”
Section: Introductionmentioning
confidence: 99%
“…POMs exert significant biological activities, with high efficacy and low toxicity. With regards to the biological activity of the POMs, many literature reports describe the activity of polyoxometalates with Keggin, lacunary Keggin, Wells-Dawson, double-Keggin and Keggin-sandwich structures against methicillin-resistant Staphylococcus aureus (MRSA) [16], Helicobacter pylori [17], SARS coronavirus (SARS-CoV) [18] and Cancer [19]. With regards to the biological activity of the POMs, many literature reports describe the activity of polyoxometalates with Keggin, lacunary Keggin, Wells-Dawson, double-Keggin and Keggin-sandwich structures against methicillin-resistant Staphylococcus aureus (MRSA) [16], Helicobacter pylori [17], SARS coronavirus (SARS-CoV) [18] and Cancer [19].…”
Section: Introductionmentioning
confidence: 99%
“…Alongside with applications of POMs in catalysis (Wang and Yang, 2015), nanotechnology (Yamase and Pope, 2006), electrochemistry (Sadakane and Steckhan, 1998), material sciences (Proust et al, 2008), and molecular magnetism (Clemente-Juan et al, 2012), POMs have also been proven to exhibit remarkable biological activity. Due to the highly negative charge, strong acidity, geometry, their use in macromolecular crystallography (Bijelic and Rompel, 2015, 2017; Molitor et al, 2017) and as antimicrobial, (Yamase, 2005; Li et al, 2016; Bijelic et al, 2018), antiviral (Judd et al, 2001), antitumor (Fu et al, 2015), antidiabetes (Nomiya et al, 2001), and antiamyloid-fibril agents (related to Alzheimer's disease) (Gao et al, 2014) has been reported so far and more attention should be given to the biological and therapeutic effect of POMs.…”
Section: Introductionmentioning
confidence: 99%
“…In general POVs, especially decavanadate, and large, highly negatively charged POMs exhibit a high activity, whereas for example the activity of Keggin type POMs is bacterial strain dependent (Bijelic et al, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of antibacterial activity of V, which have not been fully elucidated yet, include: (a) inhibition of the activity of Na + /K + -ATPase ( Fig. 11) [26,123,137,143], (b) generation of ROS ( Fig. 11), (c) impact on transport of substrates (e.g.…”
Section: Mechanisms Of the Anti-bacterial Activity Of Vanadium: A Summentioning
confidence: 99%
“…11) along with induction of potassium (K + ) outflow from the cell [137], (d) interaction with topoisomerase type II (gyrase) ( Fig. 11), which is necessary for the proper functioning of the genome and bacterial growth, with the ATP-binding site used as a target for antibacterial drugs [144,145], (e) interaction with DNA in an intercalative manner [133] resulting in modification of the DNA structure (unwinding, stiffening, and elongation of the double helix) with formation of an intercalative complex [146], (f) interaction with components of the cytoskeleton, which results in morphological alterations of bacterial cells thereby preventing proper division [137], and (g) other nonspecific mechanisms of action ( Fig. 11), with emphasis on the better bioavailability of V complexes due to the presence of a specific ligand allowing the complex to penetrate the hydrophobic lipid-rich bacteria wall [acc.…”
Section: Mechanisms Of the Anti-bacterial Activity Of Vanadium: A Summentioning
confidence: 99%